IMPLEMENTASI TEKNOLOGI BLOCKCHAIN UNTUK PENGELOLAAN DATA KESEHATAN MENGGUNAKAN METODE SMART CONTRACT - Kurniawan, Cipto; Putrawansyah, Angga; Sutabri, Tata (STKIP Persada Khatulistiwa Sintang, 2024)
The development of information technology has had a significant impact on various sectors, including the health sector. This research aims to implement blockchain technology with smart contracts in health data management to create a secure, transparent, and efficient system. The methods used include needs analysis, smart contract development, and system simulation using the Ethereum platform and IPFS-based off-chain storage. Data was collected through literature studies, interviews, observations, and system simulations. The results show that the smart contract successfully automates the process of granting and revoking data access permissions, with an average transaction time of under 2 seconds. The system ensures data security through encryption, private key-based authentication, and immutable transaction records. Off-chain storage overcomes blockchain's capacity limitations for big data such as medical imaging results, without compromising privacy. However, this research faces the challenges of high transaction fees on public blockchains and scalability of the system at large user scales. This research contributes to the development of innovative solutions for health data management with full control by patients, while improving the transparency and efficiency of the system.